Healing activity of ointment the essential oil of the Schinus molle L. “molle” in front to the wounds infected in the cattle and in mice - Alba Gonzalez, Alex (2009)
In the present investigation was evaluated the healing effect of the essential oil of Schinus molle L. “molle” to different concentrations, in comparison with a commercial product. The one was determined that the essential oil of the Schinus molle L. “molle”, mostly have monoterpenoids and sesquiterpenoids in ointment having as base solid petroleum jelly. The results mostrated what the product also has healing properties front to the wounds infected in the cattle, in which they healed of appropriate way; the carried out experiments in mice cepa Balb C 53, corroborated the mentioned experience, being the concentration to 2% that presented/displayed greater to be able healing front to the pododermatitis and reported subclinical mastitis.